Learning the ropes of technology education: the journey of older adults and tech savvy principals - Cocoba, Raymunda D. (Manila : National University, 2017)
The effect of instructional technology in education has drawn increasing attention in line with the technological advancement in this generation. As educational leaders, the principals are expected to be the key facilitator in the effort to integrate technology into the school. However, learning the technology and integrating in it professional practice is a challenging experience especially to older adult principals. With this, this study was set forth to determine how older adult principals manage to learn to use technology and to integrate it in their school management practice.
Title page -- Approval Sheet -- Dedication -- Acknowledgement -- Table of contents -- Abstract -- Chapter 1. Introduction -- Chapter 2. Review Methodology -- Chapter 3. Results and Discussion -- Chapter 4. Conclusion -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.